High-entropy alloys as a prospective class of new radiation-tolerant materials research development analysis based on the information databases - Levenets, A.V.; Tikhonovsky, M.A.; Voyevodin, V.N.; Shepelev, A.G.; Nemashkalo, O.V. (Вопросы атомной науки и техники, 2021)
A new class of metallic materials, so-called high-entropy alloys (HEAs), was under review. Various definitions of these alloys are given, their main differences from the conventional alloys are indicated and the dynamics of publications in the period from the first publications in 2004 to the end of 2020 are presented. It is noted the almost exponential growth of the article numbers concerning these alloys, and the main reasons of such high interest are discussed. Experimental results of development the radiation-tolerant materials based on the concept of high-entropy alloys and study of the radiation damage mechanisms are summarised. Розглянуто новий клас металічних матеріалів – так звані «високоентропійні сплави». Надано різні їх визначення, вказано основні відмінності цих матеріалів від традиційних сплавів, наведено динаміку публікацій за період від перших робіт у 2004 році до кінця 2020 року. Виявлено практично експоненціальне збільшення числа статей, присвячених цим сплавам, обговорено причини такої високої активності досліджень у даній області. Наведено результати розробки радіаційно стійких матеріалів на основі концепції високоентропійних сплавів, та підсумовано дослідження механізмів радіаційних пошкоджень у таких матеріалах. Рассмотрен новый класс металлических материалов – так называемые «высокоэнтропийные сплавы». Даны их различные определения, указаны основные отличия этих материалов от традиционных сплавов и приведена динамика публикаций за период от первых работ в 2004 году до конца 2020 года. Обнаружен практически экспоненциальный рост числа работ, посвященных этим сплавам, обсуждены причины такой высокой активности исследований в данной области. Приведены результаты разработок радиационно стойких материалов на базе концепции высокоэнтропийных сплавов, и просуммированы исследования механизмов радиационных повреждений в таких материалах.